Reactivation of developmentally silenced globin genes by forced chromatin looping - Deng, Wulan (2014)
Distal enhancers commonly contact target promoters via chromatin looping. In erythroid cells, the locus control region (LCR) contacts β-type globin genes in a developmental stage-specific manner to stimulate transcription. Previously, we induced LCR-promoter looping by tethering the self-association domain (SA) of Ldb1 to the β-globin promoter via artificial zinc fingers. Here, we show that targeting the SA to a developmentally silenced embryonic globin gene in adult murine erythroblasts triggered its transcriptional reactivation. This activity depended on the LCR, consistent with an LCR-promoter looping mechanism. Strikingly, targeting SA to the fetal γ-globin promoter in primary adult human erythroblasts increased γ-globin promoter-LCR contacts, stimulating transcription to approximately 85% of total β-globin synthesis with a reciprocal reduction in adult β-globin expression. Our findings demonstrate that forced chromatin looping can override a stringent developmental gene expression program and suggest a novel approach to control the balance of globin gene transcription for therapeutic applications.